Expression of Bisecting Type and Lewisx/Lewisy Terminated N-Glycans on Human Sperm - Pang,P; Tissot,B; Drobnis,EZ; Sutovsky,P; Morris,HR; Clark,GF; Dell,A (Journal of Biological Chemistry, 2007)
Human sperm lack major histocompatibility class I molecules, making them susceptible to lysis by natural killer (NK) cells. Major histocompatibility class I negative tumor cells block NK cell lysis by expressing sufficient amounts of bisecting type N-glycans on their surfaces. Therefore, sperm could employ the same strategy to evade NK cell lysis. The total N-glycans derived from sperm were sequenced using ultrasensitive mass spectrometric and conventional approaches. Three major classes of N-glycans were detected, (i) high mannose, (ii) biantennary bisecting type, and (iii) biantennary, triantennary, and tetraantennary oligosaccharides terminated with Lewisx and Lewisy sequences. Immunostaining of normal sperm showed that glycoproteins bearing Lewisy sequences are localized to the acrosome and not the plasma membrane. In contrast, defective sperm showed distinct surface labeling with anti-Lewisy antibody. The substantial expression of high mannose and complex type N-glycans terminated with Lewisx and Lewisy sequences suggests that sperm glycoproteins are highly decorated with ligands for DC-SIGN. Based on previous studies, the addition of such carbohydrate signals should inhibit antigen-specific responses directed against sperm glycoproteins in both the male and female reproductive systems. Thus, the major N-glycans of human sperm are associated with the inhibition of both innate and adaptive immune responses. These results provide more support for the eutherian fetoembryonic defense system hypothesis that links the expression of carbohydrate functional groups to the protection of gametes and the developing human in utero. This study also highlights the usefulness of glycomic profiling for revealing potential physiological functions of glycans expressed in specific cell types.